Seed productivity of different tomato varieties under the conditions of the Novosibirsk region - Tatiana V. Steinert; Zinaida P. Sinitsina; Anatoliy V. Aliluev; Lyudmila M. Avdeenko; Nadezhda S. Teplova; Valentina Yu. Poldnikova; Alexey M. Romanov (Овощи России)
Relevance Among vegetable crops, tomato is one of the leading places. In Siberia, tomato production is currently concentrated mainly in small farms and the individual sector. The problem of expanding the assortment of this culture in connection with constantly increasing market requirements remains always relevant. Material and methods The purpose of the work is the development of tomato seed production methods of varieties of selection of SibNIIRS. The studies were carried out in 2014-2018 at the experimental vegetable section of SibNIIRS - a branch of the ICG SB RAS. Results The results of many years of work on the study of seed and marketable productivity of zoned varieties and prospective tomato samples from the Urals andSiberia are presented. It has been established that in the conditions of a short growing season, high productivity is shown by varieties from early and mid-season groups. The highest sowing qualities are formed when sowing in time, optimal for the zone – the third decade of April. Early seeding shifts the phenological phases towards their rapid passage, but this creates unfavorable conditions for setting – stress during transplants, unfavorable weather. During late sowing, seeds are formed with low sowing qualities due to insufficient heat supply, especially for varieties from late ripeness groups. Germination energy and germination are higher in seeds obtained from fruits taken in the phase of full biological ripeness in all varieties. With long-term ripening (eat fruit in the phase of technical ripeness) there is a high risk of seed germination inside the fruit on the one hand and lack of nutrients, which invariably affects sowing qualities.